Medication reconciliation process in emergency department. Issue 2 (12th March 2012) - Arcenillas, P.; Vilardell, N.; Soriano, L.; March, P.; Garriga, R.; Pla, R.
Abstract : Background: Medication reconciliation is a key point of security and improvement to patient care process. Purpose: To describe discrepancies in medication reconciliation process during admission and classify drugs involved in reconciliation errors according to Anatomical Therapeutic Chemical (ATC) classification system. Materials and methods: Prospective, longitudinal study performed from January to September 2011 in a 500-bed university hospital. The pharmacist assisted the emergency department 1 h a day and checked current home medication and emergency prescription. Patients who had programmed admission at that moment were included. Medication information prior to admission was collected from electronic clinical history and patients' interview. Identified discrepancies were commented to physicians to obtain explanation. If it was necessary prescription was filled or/and modified. Quality parameters (discrepancies/patient and errors/patient) and coverage ratio (patients reviewed/admitted) recommended by Sociedad Española de Farmacia Hospitalaria were calculated. Results: 846 patients were included with an average age of 76 (limits: 34–97), 53.1% were men. Were identified 512 discrepancies in 274 patients (1.8 discrepancies/patient), 287 (56.1%) were not justified (considered reconciliation errors). Coverage ratio was 32.4%. A 63.5% (174) of patients presented at least one error (1.3 error/patient). The main error was incomplete prescription in a 30.1% (154), followed by current drug omission in 11.9% (61), different dose, administration route or frequency in 8.6% (44), wrong medication in 2.5% (13), duplicity 2.1% (11) and interaction in 0.6% (3) cases. Classifying discrepancies by ATC system, the C group presented the highest percentage with a 45.9% (235), the N group 17.8% (91), B 12.9% (66) and A 9.6% (49). The other groups represented 13.9% (71). Main drug group implicated in reconciliation error are detailed in table 1. Conclusions: Medication reconciliation is an important multidisciplinary strategy conducted by pharmacists to improve security in hospitals. A high percentage of patients presented reconciliation errors so it could be necessary that sanitary staff take in consideration its importance.